Evaluation of heavy metals contamination and pollution indices levels in surface sediments of the Bizerte coastal line, Tunisia. (November 2022) - Aydi, Abdelwaheb; Ghannem, Samir; Nasri, Ahmed; Hessine, Rania; Mezni, Amine
Abstract: Heavy metal concentrations in surface sediments collected from 17 stations samples in Bizerte coastal line were determined in order to evaluate the contamination status in the region. Heavy metal concentrations (mg/kg) of Bizerte coast line followed the decreasing trend of Fe > Pb > Zn > Mn > Cu > Cr > Ni > Co > Cd. The pollution degree of the surface sediment collected from 17 samples station in Bizerte coast line by heavy metals was evaluated on the basis of pollution indices (EF, Igeo, CF, PLI and CD). Results of Igeo, EF, CF, PLI and DC demonstrated that pollution levels of Pb and Cd were moderate, which should require more attentiveness as main pollution factors. However, no pollution was found for Zn, Cu, Ni, Cr, Co and Mn. Hierarchical cluster analysis was used to identify the influence of anthropogenic activities on the surface sediment. Highlights: Heavy metal (HM) concentrations in surface sediments collected from 17 stations samples in Bizerte coastal line. HM was evaluated on the basis of, a EF, Igeo, CF, PLI and DC. These results can be used as a useful tool for future monitoring of heavy metals pollutant.